Narracja w biografii: od ustanawiania sensu do budowania relacji - Całek, Anita (Zagadnienia Rodzajów Literackich, 2021)
The article discusses the concept of Olga Tokarczuk’s “tender narrator”, which was demonstrated in her Nobel speech, and developed in a book entitled “Tender Narrator” (Tokarczuk 2020). The writer’s proposed way of describing the narrative and narrator was used to examine the concept of the biographical narrator, his bond with a hero, the truth and the fiction in the biography, the process of discovering and finding a purpose to existence. Olga Tokarczuk’s idea was discussed in the context of other useful theories aimed at the search for meaning: a reference to the concept of the course of life of Charlotte Bühler (1933/1999) and the will to make sense of Viktor E. Frankl (1948/2018, 1982/2017, 1988/2018, 1992/2018) allowed us to see a common ground for reflection on the role and specificity of biographical narrative. On the one hand, Agata Bielik-Robson’s concept (2004) on the trauma of the present highlighted the need for retrospective life storytelling and its therapeutic, reparative nature. On the other hand, the personalistic norm (in its original sense proposed by Karol Wojtyła in “Love and Responsibility” of 1986), according to which the only appropriate way to refer to a person is love, turned out to be close to the model of “tender narrator”. The extensive conceptualization of that idea, proposed by Olga Tokarczuk, compared to the concept of biographical narrator and the concepts mentioned above, allows for a reconsideration of the important issues discussed earlier: the “tender narrator” model turned out to be inspiring for attempts to rethink the adequacy of biographical representation, the objectivity vs. involvement of a biographer, and the relationship between biography and literature.